PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IVc SD NEGERI 30 DURI BARAT KECAMATAN MANDAU - Ariyanti Ariyanti; Zuhri D Zuhri D; Jalinus Jalinus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This research aims to improve the learning process and improve learning outcomes mathematics of the fourth-c grade students of SDN 30 Duri Barat Kecamatan Mandau by implementing cooperative learning type TSTS. The subjects were students of class fourth-c grade whom have heterogeneous academic ability. This research is a class act with two cycles. Each cycle has three times and one UH in every end cycle and has four stages, the stages are planning, implementation, observation, and reflection. The results of the research show the observation sheet activities of teacher and students have done after the action. The increasing  number of students who achieve at UH KKM in the end of every cycle compared to the number of students who achieve a score a KKM on basic score. This results of this study indicate that the application of cooperatif learning type TSTS can improve the process learning and improve the learning outcomes of the fourth-c grade students of SDN 30 Duri Barat Kecamatan Mandau in the odd semester academic year 2013/2014. Key words : Learning process, Mathematic learning outcomes, Cooperative learning, TSTS, Classroom action research.